Pancreatic Mucinous Cystic Neoplasm with Associated Invasive Carcinoma: A Case Report and Literature Review - Marcinkeviciute, Kristina; Jurkeviciute, Digne; Stulpinas, Rokas; Stratilatovas, Eugenijus; Dulskas, Audrius (Lietuvos chirurgija, 2023)
Background. Pancreatic mucinous cystic neoplasm (PMCN) with associated invasive carcinoma is a rare entity. According to the World Health Organisation (WHO) 2010, PMCN with associated invasive carcinoma is referred to the malignant lesions of the pancreatic epithelial tumour. Case report. A 52-year-old female patient presented with pain in the umbilical and epigastric regions for 5 months and noticed a solid visible tumour on the left side of the abdomen 3 months ago when she lied down. The level of the CA125 was 47.64 U/ml (normal value
Keywords: pancreatic mucinous cystic neoplasm; IPMN; invasive carcinoma of the pancreas; pancreatic lesions; pancreatic cancer; mucinous cystic neoplasms; case report